2015
DOI: 10.4103/1463-1741.169701
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward noise, perceived hearing symptoms, and reported use of hearing protection among college students: Influence of youth culture

Abstract: The purpose of this study was to assess the attitude toward noise, perceived hearing symptoms, noisy activities that were participated in, and factors associated with hearing protection use among college students. A 44-item online survey was completed by 2,151 college students (aged 17 years and above) to assess the attitudes toward noise, perceived hearing symptoms related to noise exposure, and use of hearing protection around noisy activities. Among the participants, 39.6% experienced at least one hearing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 35 publications
8
54
1
Order By: Relevance
“…15 In relation to noise, those who have experienced hearing symptoms (e.g., tinnitus, noise sensitivity, or temporary hearing loss) are more likely to have negative attitudes toward noise and loud levels of music, 16 and they are therefore more likely to use hearing protection than those who have positive attitudes toward noise. 17,18 However, experiencing hearing problems is not always a motivator for hearing protection. Recent studies in the United Kingdom and Belgium found a high prevalence of temporary NIHP in students, 14,19 and yet the use of hearing protection was minimal and the majority said the risk of hearing damage would not affect their nightclub attendance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…15 In relation to noise, those who have experienced hearing symptoms (e.g., tinnitus, noise sensitivity, or temporary hearing loss) are more likely to have negative attitudes toward noise and loud levels of music, 16 and they are therefore more likely to use hearing protection than those who have positive attitudes toward noise. 17,18 However, experiencing hearing problems is not always a motivator for hearing protection. Recent studies in the United Kingdom and Belgium found a high prevalence of temporary NIHP in students, 14,19 and yet the use of hearing protection was minimal and the majority said the risk of hearing damage would not affect their nightclub attendance.…”
mentioning
confidence: 99%
“…[21][22][23] A study in the United States found that less than 10% of college students reported using hearing protection for rock concerts, discos, and sporting events. 18 Perceived individual susceptibility to hearing damage and perception of risk is likely to be one factor influencing earplug use. An online survey of Australian young adults found that those who engaged in noisy activities showed early signs of hearing damage, 24 and although some recognized the risk associated with noise exposure, few had started to reduce that risk by using earplugs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 A secondary aim of this study was therefore to analyze self-reported outcomes that may influence earplug use during a music festival. We intended to gain insights in the behavior of music festival attendees during a festival visit, including earplug use and the time spent near stages and loudspeakers as well as alcohol and drug use.…”
mentioning
confidence: 99%
“…Schools are privileged spaces for implementation of public policies, especially health education ones, as they allow the promotion of auditory health and prevention of hearing loss in adolescents (10,11) .…”
Section: Introductionmentioning
confidence: 99%